2023
DOI: 10.1093/plcell/koad010
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA-mediated DNA methylation during plant reproduction

Abstract: Reproductive tissues are a rich source of small RNAs, including several classes of short interfering (si)RNAs that are restricted to this stage of development. In addition to Pol IV-dependent 24-nt siRNAs that trigger canonical RNA-directed DNA methylation (RdDM), abundant reproductive-specific siRNAs are produced from companion cells adjacent to the developing germ line or zygote and may move intercellularly before inducing methylation. In some cases, these siRNAs are produced via non-canonical biosynthesis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 142 publications
1
13
0
Order By: Relevance
“…Along with DNA methylation, DNA demethylation pathway players, such as demethylase DME in Arabidopsis and ROS1a in rice central cells, were also implicated in imprinting across plants (Xiao et al, 2003; Gehring et al, 2006; Kim et al, 2019). One of the crucial players in plant epigenetics are sRNAs and their expression drastically increases in reproductive tissues (Chow and Mosher, 2023; Hari Sundar G et al, 2023). Unlike Arabidopsis , other dicots like B. rapa and Capsella RdDM mutants showed pollen and seed abnormalities (Mosher et al, 2009; Grover et al, 2018; Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Along with DNA methylation, DNA demethylation pathway players, such as demethylase DME in Arabidopsis and ROS1a in rice central cells, were also implicated in imprinting across plants (Xiao et al, 2003; Gehring et al, 2006; Kim et al, 2019). One of the crucial players in plant epigenetics are sRNAs and their expression drastically increases in reproductive tissues (Chow and Mosher, 2023; Hari Sundar G et al, 2023). Unlike Arabidopsis , other dicots like B. rapa and Capsella RdDM mutants showed pollen and seed abnormalities (Mosher et al, 2009; Grover et al, 2018; Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While the rules governing such competition remain to be elucidated, presuming some CLSYs are preferred over others, it would add another dimension to their regulation of DNA methylation. Past studies already demonstrated that the CLSYs are differentially expressed during development and that they target Pol IV to distinct genomic targets 10,20 , resulting in tissue-specific methylation patterns and links between specific CLSYs and several epigenetically regulated traits 16,62 . Within this context, our discovery of a CLSY docking motif in Pol IV suggests a new layer of regulation that could control DNA methylation patterns: competition for binding to the Pol IV complex.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of 24-nt siRNA was related to the level of TE methylation in B. napus Plants achieve TE silencing and maintain genome stability through DNA methylation. The RdDM pathway acts primarily on TEs and is vital for methylation maintenance (Chow & Mosher, 2023), while siRNA is an essential component of the RdDM pathway. In order to further explore the influence of epigenetic modifications on TE methylation during allopolyploidization, we analyzed the regulatory role of the RdDM pathway in TE methylation in combination with small RNA data.…”
Section: Allopolyploidization Affected the Dna Methylation Level Of Tesmentioning
confidence: 99%
“…DNA methylation is conserved in the genome, and abnormal changes can cause developmental failure in plants and animals, as well as embryo lethality (Zhang et al., 2018). In plants, the RNA‐directed DNA methylation (RdDM) pathway mediates de novo DNA methylation, mainly acting on short TEs and DNA near TEs, and is involved in many biological functions such as pathogen defense, stress response, reproduction, and genome interaction (Burgess et al., 2022; Chow & Mosher, 2023; Matzke & Mosher, 2014; Zemach et al., 2013; Zhang et al., 2018). As a critical component of the RdDM pathway, 24‐nt siRNAs are the most abundant small RNA in plant genomes (Chow & Mosher, 2023), direct TE methylation to regulate gene expression, and control rice tillering and stress resistance (Sun et al., 2021; Xu et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation